Penunggang Kuda Putih Itu Adalah Ida Sang Hyang Yesus Kristus, Sang Awatara: Perjumpaan Kristen Bali dengan Kitab Wahyu di Sulawesi Tengah - I Gede Supradnyana (Indonesian Journal of Theology, 2015)
In this essay, I present an understanding of Jesus from the perspective of Balinese Christians in Central Sulawesi. As an example of a reader-response method, Revelation 19:11-21 has been historically read there in light of a Balinese worldview. Such readings meet with the Balinese interpretation of the white-horse rider (Jesus) as the awatara (avatar) that will come again to fight evil (adharma) and to establish righteousness (dharma) on earth. Insights to be culled from such work include increased awareness of our ecological plight, as well as heightened urgency to address both the moral decline of society and the contemporary phenomenon of indifference toward religion.